Imaging of the Spine: A Bibliometric Analysis of the 100 Most-Cited Articles. Issue 22 (15th November 2019) - Das, Jeeban Paul; Aherne, Emily; Kavanagh, Eoin
Abstract : Study Design: A bibliometric review of the literature. Objective: The aim of this study was to identify the most highly cited articles relating to imaging of the spine and to analyze the most influential papers and evolving trends in spinal imaging research. Summary of Background Data: Spinal imaging is being performed with increasing frequency and is an essential step in the diagnosis and treatment planning of spinal pathology. A comprehensive review of the most influential articles in spinal imaging has not been performed, until now. Methods: A selection of search terms and keywords were inputted into the "Web of Science" database and the most highly cited articles in spinal imaging were selected from high impact factor journals. The top 100 articles were analyzed for year of publication, authorship, publishing journals, institution and country of origin, subject matter, article type, and level of evidence. In addition to total citation count, the number of annual citations was also calculated. Citation counts from Scopus and Google Scholar were also obtained for comparison across other citation index platforms. Results: The most highly cited articles in spinal imaging were published over 30 years, between 1983 and 2013. Total citation count ranged from 98 to 1243 with annual citation count ranging from 3.8 to 91.8. The greatest number of highly cited articles was produced in the United States (n = 49), involved magnetic resonance (n = 73) or multimodal (n = 17) imaging and focused on the lumbar spine (n = 42). The journals that contributed the most articles were Spine and Radiology each publishing 26 articles. Conclusion: Our study provided an extensive list of the most historically significant spinal imaging articles, acknowledging the key contributions made to the advancement of this specialist field. Level of Evidence: 5 Abstract : Supplemental Digital Content is available in the textA bibliometric analysis of the top 100 most-cited spinal imaging articles was performed. Total citation count ranged from 98 to 1243. Spine and Radiology published 52% of these articles. We provide a useful list of influential spinal imaging articles for clinicians and researchers with an interest in this specialist field.